Thoracoscopic Surgery in a Patient with Multiple Esophageal Carcinomas after Surgery for Esophageal Achalasia. (30th August 2017) - Yamasaki, Yuki; Tsukada, Tomoya; Aoki, Tatsuya; Haba, Yusuke; Hirano, Katsuhisa; Watanabe, Toshifumi; Kaji, Masahide; Shimizu, Koichi
Abstract : We present a case in which we used a thoracoscopic approach for resection of multiple esophageal carcinomas diagnosed 33 years after surgery for esophageal achalasia. A 68-year-old Japanese man had been diagnosed with esophageal achalasia and underwent surgical treatment 33 years earlier. He was examined at our hospital for annual routine checkup in which upper gastrointestinal endoscopy showed a "0-IIb+IIa" lesion in the middle esophagus. Iodine staining revealed multiple irregularly shaped iodine-unstained areas, the diagnosis of which was esophageal carcinoma. Thoracoscopic subtotal esophagectomy was performed. Esophageal carcinoma may occur many years after surgery for esophageal achalasia, even if the passage symptoms have improved. So, long-term periodic follow-up is necessary for detection of carcinoma at an earlier stage.